Influence of Primers and Additional Resin Layer on Zirconia Repair Bond Strength. Issue 7 (22nd January 2019) - Shafiei, Fereshteh; Fattah, Zahra; Kiomarsi, Nazanin; Dashti, Mohammad Hossein
Abstract: Purpose: To evaluate the influence of alloy/zirconia primer and 10‐methacryloyloxydecyl dihydrogen phosphate (MDP)‐containing resin layer treatments on the shear bond strength (SBS) of composite resin to zirconia after aging. Materials and Methods: Sixty zirconia (Y‐TZP) blocks were air‐abraded (35‐µm Al2 O3 ) and divided into 6 experimental groups (n = 10) in terms of primer/resin layer as follows: (1) control, without any primer or resin; (2) AP, Alloy Primer; (3) ZPP, Z‐Prime Plus; (4) PL/ZPP, Z‐Prime Plus with light polymerization; (5) AP+SEB, Alloy Primer along with light‐cured bonding resin of a self‐etch adhesive system (SE Bond); and (6) ZPP+SEB, Z‐Prime Plus with SE Bond. After composite resin placement and light polymerization, the specimens were stored in distilled water (37°C for 4 months) and thermal‐cycled for 6000 cycles. The SBS was tested with a universal testing machine. Statistical analysis of the SBS data was performed with one‐way ANOVA, followed by HSD Tukey test (α = 0.05). Results: There were significant differences between the groups ( p < 0.001, F = 116.5). All the groups revealed significantly higher SBS than the control ( p < 0.001). ZPP+SEB group exhibited the highest SBS (16.14 ± 2.52 MPa) and AP group the lowest SBS (7.00 ± 1.97 MPa) among experimental groups; both had significant differences with the other groups ( p < 0.001). There were no significant differences between ZPP, PL/ZPP, and AP+SEB groups ( p > 0.05). Conclusions: The bond strength between zirconia ceramic and composite resin was affected by different primers/resin layer. Applying an MDP‐containing resin layer along with both primers resulted in significant enhancement of SBS. This improvement for Z‐Prime Plus was significantly higher than that of Alloy Primer.